Structural analysis by DRX of a modified colombian natural clay by pillaring (Revista de Investigaciones Universidad del Quindío, 2013)
The clay mineral sample used in this study was extracted from a deposit located in Moñitos (Córdoba, Colombia), which was modified by pillaring using aluminum [Al13O4(OH)24(H2O)12]7+, aluminum-iron and aluminum- cerium polioxocationic species.The obtained materials, referred to as Al-PILC, Fe-Al-PILC and Al-Ce-PILC were studied by X-ray diffraction (XRD) in order to determine certain characteristics such as swelling capability, nature of clay, mineral phases, basal spacing and analysis of the observed variations.The diffractograms of pillared samples denotes a shift of the signal corresponding to (001) plane, as a result of increase in the interlayer spacing, consequence of the inclusion of Al, Al-Fe and Al-Ce pillars in the sheets clay.
Keywords: smectite; pillared clay; x-ray diffraction; basal spacing